Chronic Noise Exposure and Risk of Dementia: A Systematic Review and Dose-Response Meta-Analysis - Meng, Linghao; Zhang, Yang; Zhang, Shushan; Jiang, Fugui; Sha, Leihao; Lan, Yajia; Huang, Lei (Frontiers in Public Health, 2022)
Objective: Evidence is scarce about the effect of noise exposure on the risk of dementia. We conducted a systematic review and dose-response meta-analysis, aiming to explore the association between noise exposure and the risk of dementia. Methods: We searched PubMed, EMBASE and the Cochrane Library to collect studies on chronic noise exposure and the risk of dementia from database inception to September 18, 2021 without language limitations. Two authors independently screened the literature, extracted data and assessed the risk of bias of the included studies. A dose-response meta-analysis and subgroup analysis were then conducted to detect the association between noise exposure and the risk of dementia by using Stata 14.0 software. This study is registered on PROSPERO (CRD42021249243). Results: A total of 11 studies were eligible for qualitative synthesis, and nine were eligible for quantitative data synthesis. All of them showed moderate to high quality scores in the assessment of risk of bias. We found a positive linear association between the noise increment and dementia risk (R2=0.58). When noise exposure increased 57 dB, the RR of dementia was 1.47 (95% CI: 1.21-1.78). From the outcome subgroup of AD, AD and dementia, VaD and NAD, we also found a positive association (R2=0.68, 0.68, 0.58, respectively). When noise exposure increased by 25 dB, the RRs were 1.18 (95% CI: 1.14-1.23), 1.19 (95% CI: 1.14-1.23) and 1.17 (95% CI: 1.06-1.30), respectively. We found a nonlinear association between the noise increment and dementia risk when only cohort studies were included (R2=0.58). When noise exposure increased by 25 dB, the RR of dementia was 1.16 (95% CI: 1.12-1.20). From the subgroup of AD, AD and dementia, VaD and NAD of cohort studies, the regression curve showed a nonlinear positive association (R2=0.74, 0.71, 0.43, respectively). When noise exposure increased by 25 dB, the RRs were 1.17 (95% CI: 1.12-1.21), 1.17 (95% CI: 1.12-1.22) and 1.13 (95% CI: 0.99-1.28), respectively. Conclusion: Based on the current evidence, exposure to noise may be a specific risk factor for dementia. To better prevent dementia, more rigorously designed studies are needed to explore the etiological mechanism of noise and dementia.